Simulation of the Meander Delay Line using the Hybrid Method - Urbanavičius, V.; Gurskas, A.; Martavičius, R. (Elektronika ir Elektrotechnika, 2009)
The hybrid method of analysis of the microstrip meander delay line (MMDL), which takes into account non-periodicity of electrical parameters along the meander structure, is proposed. Three known methods of analysis are used for creation of the hybrid method: the method of multi-conductor lines, the method of moments and the scattering matrixes approach. The MMDL model in the proposed method is created using a multi-conductor line of the corresponding design, electric parameters of the multi-conductor line are calculated using the method of moments, and conductors of the multi-conductor line are connected to form the meander structure, which in turn is analyzed by scattering matrixes. The created method takes into account non-periodicity of electric parameters of strips of the meander and allows finding characteristics of MMDL precisely enough. The accuracy of the proposed hybrid method was verified. Calculated basic dynamic characteristics of the MMDL in frequency domain showed good coincidence with the experimentally measured results. Ill. 7, bibl. 21 (in English; summaries in English, Russian and Lithuanian).